Unsteady thermoelastic analysis of a circular disk with a hot central core and subjected to adiabatic conditions - Rossit, Carlos Adolfo (2000)
The unsteady thermoelastic analysis of a cooling circular disk or cylinder which is originally at uniform temperature is a classical problem of the theory of thermal stresses. More recent studies consider the case of composite structural configurations. The present paper deals with a situation which, apparently, has not been previously considered: unsteady thermal stresses caused by the presence of a hot, central nucleus. The temperature field is obtained in terms of a Fourier–Bessel expansion and then, radial and tangential stresses are evaluated analytically. The problem is of basic interest in mechanical and naval engineering systems.